LINGUOCULTURAL ANALYSIS OF PHRASES WITH THE CONCEPT OF KNOWLEDGE IN ENGLISH LANGUAGES - Narmuratov Zayniddin Radjabovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation. This article explores the linguistic and cultural underpinnings of English phrases related to the concept of knowledge. By analyzing common idiomatic expressions and sayings, the study highlights how cultural values, historical context, and societal attitudes are embedded in language. The research aims to provide insight into how the English-speaking world conceptualizes knowledge, emphasizing the interconnection between language and culture.